OPTIMALISASI PODCAST DAN INTEGRASI PODCAST KE PEMBARUAN SISTEM INTI ADMINISTRASI PERPAJAKAN DALAM RANGKA MENINGKATKAN KESADARAN WAJIB PAJAK ORANG PRIBADI NON KARYAWAN - Auliya Rahman, Rheza; Hamdi, Auza; Yudhatama Iswahyudi, Hendriko (Politeknik Keuangan Negara STAN, 2025)
Podcasts are a communication medium that is currently popular and can be a means of socializing taxation. However, the Directorate General of Taxes' podcast is currently not fully optimal. Therefore, efforts are needed to optimize podcasts in order to increase awareness of non-employee individual taxpayers. Using qualitative methods through literature study, observation, and netnography, it was found that efforts to optimize podcast broadcasts in order to increase awareness of Non-Employee Individual Taxpayers took the form of limiting the duration of the podcast to 10 to 20 minutes, including MSMEs as podcast sources, adding subtitles, and integrating podcast content to the PSIAP website.